Linear Lichen Planus in the Setting of Annual Vaccination. Issue 5 (12th September 2018) - Hardy, Curtis; Glass, Jonathan
Abstract: Vaccines have a well-demonstrated therapeutic benefit. However, the spectrum of potential dermatologic vaccine side effects ranges from localized skin irritation to acute and delayed response. Currently, there are limited published data correlating dermatoses with alterations in the immune system following vaccination. The mechanism by which group A beta-hemolytic streptococci may precede the manifestation of guttate psoriasis is included as a mechanism foundation as we further describe the immunopathogenesis of immune-mediated linear dermatoses. We present a rare case of linear lichen planus following intramuscular influenza vaccination, not associated with an injection site reaction. Immune-related dermatoses may be underreported, and a vaccine history should be considered in all patients with a skin condition that is otherwise attributed as idiopathic.